The Crash Course from Iceland - Huginn Freyr Þorsteinsson (The University of Akureyri, 2014)
The years between 2006 and 2008 are key in understanding the Icelandic economic crisis. One of the main questions one gets when discussing the lessons from Iceland is: Was the quick recovery due to how the country 'burned' the creditors? Myth has it that when things got tough for the banks, the Icelandic government denied to bail them out and the country therefore escaped the difficult long-term consequence felt by, for example, Ireland. But that is a serious distortion of what happened. The Icelandic banks were on Central Bank life support from 2006 to 2008. It was only when the CBI ran out of steam that an alternative approach in crisis management was put in place. For admirers of historical contingencies, this case is of interest. Iceland did not take a calculated decision to let the banks fail, but an attempted bail-out failed. This meant that that its tackling of a banking crisis took an unexpected turn as banks were put into administration; a move only considered in the face of failure. And despite the route taken by Iceland, the total cost of the economic crisis for the State has surpassed Ireland's and is one of the costliest any sovereign has faced in the ongoing crisis. This is interesting, given the ongoing discussion about the Icelandic 'miraculous' escape from an economic crisis and that the possibilities countries face during crisis management may be many more than those that are discussed.